The Comparative Study Between Readable and Let’s Read Applications toward Students’ Reading Skill - Rodiatul Mutmainah; Ilzamudin Ma’mur; Purnama Rika Perdana (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Since English is an international language and a foreign language to Indonesians, mastering it is essential. These days, learning English is quite simple. People are aware of Mobile-Assisted Language Learning (MALL), which uses mobile technology to teach language skills and extends learning in a new environment. This study compared the effectiveness of Readable and Let’s Read applications in improving students’ reading skill. Using qualitative research, the participants are three students of STAIDAZ (Sekolah Tinggi Ilmu Tarbiyah Darel Azhar). Both programs make use of Mobile-Assisted Language Learning (MALL) resources to enhance reading comprehension and fluency. Considering their varied characteristics, both applications aim to improve students’ reading skills.